2015
DOI: 10.1007/s12517-015-2083-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of stream flow and precipitation regimes on water quality of the major inflow stream of Wular Lake in Kashmir Himalaya

Abstract: Wular Lake in the Kashmir Himalayan part of the Indian subcontinent is facing severe eutrophication due to the enhanced nutrient loads from its catchment. For holistic management of this lake, quantifying the nutrient loads from all of its inflow streams is compulsory for establishing a scientific basis for managing its highest loading watersheds. The present work has been carried out in the Sukhnag stream and is one of the major inflow streams of the Wular Lake. The analyses presented hereof are the initial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Zhang et al (2010), Moss (2012), and Yadav and Pandey (2017), have shown how built-up contributes to the increased nutrient loads in the lake, thus increasing the concentration of these WQ parameters. We observed that there is an increase in average decadal COD, NO 3 -N, and TP in the Dal Lake and is reflected with negative correlation between changes in the agricultural area and these water quality parameters (Bhat et al 2016) ( Fig. 10a-e; Tables 3, 4).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Zhang et al (2010), Moss (2012), and Yadav and Pandey (2017), have shown how built-up contributes to the increased nutrient loads in the lake, thus increasing the concentration of these WQ parameters. We observed that there is an increase in average decadal COD, NO 3 -N, and TP in the Dal Lake and is reflected with negative correlation between changes in the agricultural area and these water quality parameters (Bhat et al 2016) ( Fig. 10a-e; Tables 3, 4).…”
Section: Discussionmentioning
confidence: 82%
“…Changes in LULC have a significant influence on earth system processes such as hydrology, climate, biogeochemical cycles resulting in adverse environmental issues if promulgated unfettered (Bhat et al 2013(Bhat et al , 2014(Bhat et al , 2016. Globally, LULC changes have resulted in deforestation, biodiversity loss, global warming, and an increase in natural disasters, hence causing global environmental change (Hooijer et al 2004;Altaf et al 2013;Meraj et al 2013Meraj et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Geogenic species (e.g., Na, Mg, and Si) derived from chemical weathering have demonstrated widespread chemostatic behavior (Godsey et al, 2009). Yet exceptions do exist, manifesting significant dilution of Ca and Na in regions with high runoff (Moon et al, 2014) and flushing patterns of Ca, Mg, and Na at a site where cation-rich water from silicate weathering in shallow layers contributed most to the stream at high flows (Bhat et al, 2016). For dissolved organic carbon (DOC), flushing behaviors are commonly observed (Boyer et al, 1997;Musolff et al, 2017), although slight dilution is notable where net primary productivity or carbon source are limited (Zarnetske et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Hill [14] in southern Ontario, where the lowest total dissolved solid content was found in February (due to lower runoff ), whilst the highest was found in May (due to much larger runoff from watersheds). Many previous studies have revealed that major pollutant compositions in surface waters can be controlled by the interactions between precipitation and both surface-geological and biological materials [8,12,23]. The temporal concentrations of TN, TP, COD Mn , and NH 4 -N in streams and lakes are primarily governed by discharge; these increase with flow [18].…”
Section: Discussionmentioning
confidence: 99%